Performance of four cardiac output monitoring techniques vs. intermittent pulmonary artery thermodilution during a modified passive leg raise maneuver in isoflurane-anesthetized dogs - Paranjape, Vaidehi V.; Henao-Guerrero, Natalia; Menciotti, Giulio; Saksena, Siddharth (Frontiers in Veterinary Science, 2023)
This study investigated the performance among four cardiac output (CO) monitoring techniques in comparison with the reference method intermittent pulmonary artery thermodilution (iPATD) during a modified passive leg raise (PLRM) maneuver in isoflurane-anesthetized dogs undergoing acute blood volume manipulations. The study also examined the simultaneous effect of performing the PLRM on dynamic variables such as stroke distance variation (SDV), peak velocity variation (PVV), and stroke volume variation (SVV). Prospective, nonrandomized, crossover design Six healthy male Beagle dogs The dogs were anesthetized with propofol and isoflurane and mechanically ventilated under neuromuscular blockade. After instrumentation, they underwent a series of sequential, nonrandomized steps: Step 1: baseline data collection; Step 2: removal of 33 mL kg−1 of circulating blood volume; Step 3: blood re-transfusion; and Step 4: infusion of 20 mL kg−1 colloid solution. Following a 10-minute stabilization period after each step, CO measurements were recorded using esophageal Doppler (EDCO), transesophageal echocardiography (TEECO), arterial pressure waveform analysis (APWACO), and electrical cardiometry (ECCO). Additionally, SDV, PVV, and SVV were recorded. Intermittent pulmonary artery thermodilution (iPATDCO) measurements were also recorded before, during, and after the PLRM maneuver. Statistical analysis was performed using one-way analysis of variance for repeated measures with post hoc Tukey test, linear regression, Lin’s concordance correlation coefficient (ρc), and Bland–Altman analysis. Statistical significance was set at p < 0.05. The percentage error for TEE, ED, and EC was less than 30% but exceeded 55% for APWA. While TEECO and ECCO slightly underestimated iPATDCO values, EDCO and APWACO significantly overestimated iPATDCO values. TEE and EC exhibited good and acceptable agreement with iPATD. Conclusion and clinical relevance: iPATD, EC, TEE, and ED effectively assessed FR in hypovolemic dogs during the PLRM maneuver, while the performance of APWA was unacceptable and not recommended. SVV, SDV, and PVV could be used to monitor CO changes during PLRM and acute blood volume manipulations, suggesting their potential clinical utility.